RELATIONSHIPS BETWEEN THE CHEMICAL AND ISOTOPIC (Sr, Nd, Hf, AND Pb) HETEROGENEITY OF THE MANTLE - Kostitsyn Yu.A. (My University, 2007)
The reasons for the isotopic heterogeneity of the mantle are analyzed in this paper on the basis of published isotopic data. It was shown that the observed variations in the Sr, Nd, Hf, and Pb isotopic compositions of oceanic basalts cannot be explained by mixing of a finite number of homogeneous reservoirs (components). The considerable variations in the contents of Rb, Sr, Sm, Nd, Lu, Hf, U, Th, and Pb and ratios of these and other trace elements in tholeiitic basalts indicate that the chemical heterogeneity of mantle-derived rocks is inherited in part from their sources. Oceanic tholeiitic basalts show a tight correlation between the variances of Nd, Hf, Sr, and Pb isotopic ratios and the variances of respective radiogenic additions that could be accumulated in these rocks over a time period of 〈t〉 = 1.8 Gyr. This paradox clearly indicates that variations in all the mentioned isotopic systems in the mantle cannot be understood without the analysis of the geochemical heterogeneity of rocks. The close to lognormal distributions of lithophile trace elements in oceanic tholeiitic basalts and the character of correlations between them suggest that magmatic differentiation was the major mechanism of the formation of chemical heterogeneity in the mantle. The role of metasomatism in the global transport of trace elements and formation of the geochemically heterogeneous mantle is probably rather limited. Intrusive processes within the mantle could result in the development of chemical and, after a period of time, isotopic anomalies in the mantle. Simple calculations show that long-lived geochemical anomalies related to alkaline magmatism could be responsible for EM-I type isotopic anomalies, and geochemical anomalies produced in the mantle by enriched tholeiitic melts could be sources of EM-II type isotopic anomalies. The analysis of the distribution of the isotopic compositions of mantle-derived igneous rocks in various “isochron” coordinates suggested that the formation of geochemical anomalies in the mantle is a long-term process lasting for hundreds of millions of years. Nonetheless, trends approaching 4.5 Ga were never observed in such diagrams, i.e., the mantle is in general rejuvenated in all isotopic systems. Both on global and local scales, there are no mantle domains that have remained geochemically closed and isolated since the Earth’s formation. The entire mantle is involved in material exchange processes. The development of isotopic systems in the mantle was explored by means of statistical modeling accounting for the tendency of a continuous increase in the chemical heterogeneity of the mantle source and the tendency of obliteration of the isotopic heterogeneity owing to the convective mixing in the mantle. The modeling demonstrated that the character of the isotopic heterogeneity of the mantle is statistically consistent with the character of its chemical heterogeneity. The mantle isotopic anomalies HIMU, EM-I, and EM-II were generated by two simultaneous processes: the magmatic differentiation of mantle material and its not very efficient mixing.